LLC Laser Driver for Laser Wireless Power Transfer Application - Yigit, Hayri; Boynuegri, A. Rifat; Tekgun, Burak (IEEE, 2024)
Laser Wireless Power Transfer (LWPT) represents a cutting-edge technology for the long-range transmission of energy, distinguished by its capability for high-power transfer and adaptability to mobile applications. The effectiveness of this system is significantly tied to its transmitter component, comprising the Laser Diode (LD) and its associated driving circuitry. This research address to enhance system efficiency by introducing a specially designed LLC converter circuit, aimed at improving the overall efficiency of both the driver circuit and the LD driving process while minimizing current ripple. The proposed circuit underwent comprehensive simulation using MATLAB/SIMULINK, resulting in noteworthy outcomes that showcased an impressive efficiency of 98.44% within the LD driver circuit.
Boynuegri, Ali Rifat/0000-0003-4734-3126; Yigit, Hayri/0000-0003-3936-8649;
Keywords: Laser Power Transfer; LLC Converter; Laser Diode LD Driver; Wireless Power Transfer